Makna Deiksis dalam Puisi Bithoqoh Huwiyah Karya Mahmoud Darwish: Kajian Pragmatik - Azza Shofia Rahmada; Abdul Muntaqim Al Anshory (Universitas Sebelas Maret, 2025)
Mahmoud Darwish's poem Bithoqoh Huwiyah reflects the Palestinian people's struggle to maintain their identity amidst the prolonged conflict with Israel. This research departs from the main question: how deixis elements in this poem, such as the use of the words